Analysis of the Spatial and Temporal Differences of China’s Power Carbon Footprint - Zhen-Yu Zhao; Shu-Guang Yuan; Yu Fu; Ying Wang; Heng Li (Journal of Electrical and Computer Engineering)
Thermal power generation has increased CO2 emissions, which in turn has put tremendous pressure on the environment. Therefore, analyzing the regional ecological environmental carrying capacity of thermal power carbon emissions is of great significance for countries with high thermal power capacity to guide the development of low-carbon power and industrial layout. To accurately measure the pressure of regional power production for the environment, this paper proposes the concept of renewable energy virtual carbon emission based on the carbon footprint theory. The regional power carbon footprint (PCF) depth model and the regional power carbon deficit model are constructed. Moreover, through the statistics of China’s power production, this paper calculates the depth of China’s PCF and analyzes the temporal and spatial differences of China’s PCF depth from the three aspects of regional power installation structure, power deficit, and PCF transfer. The results obtained illustrate, firstly, that China’s overall PCF continues to increase, with the depth of PCF moving eastward. Secondly, due to the imbalance of China’s PCF, there are significant temporal and spatial differences in the depth of regional PCF. Thirdly, with the rapid development of renewable energy in China, the effect of controlling the depth of regional PCF by renewable energy is rising. Besides, the transfer of PCF among different China’s regions has significant impact on the change of PCF depth of power output provinces.